Atypical Social Attention and Emotional Face Processing in Autism Spectrum Disorder: Insights From Face Scanning and Pupillometry - Reisinger, Debra L.; Shaffer, Rebecca C.; Horn, Paul S.; Hong, Michael P.; Pedapati, Ernest V.; Dominick, Kelli C.; Erickson, Craig A. (Frontiers in Integrative Neuroscience, 2020)
Social attention deficits are a hallmark characteristic within ASD and have been hypothesized to have cascading effects on emotion recognition. Eye tracking methodology has emerged as a potentially reliable, feasible, and sensitive biomarker for examining core phenotypic features of ASD; however, findings are mixed with regards to measuring treatment change in clinical trials. The present study aimed to assess the utility of an eye tracking paradigm to discriminate between clinical groups in social attention and emotion recognition through visual scanning and pupillometry. The present study also assessed the reliability of this paradigm within the ASD sample to further our understanding of the utility of eye tracking for future clinical trials. Participants included 36 individuals with ASD, 28 developmental disability (DD) controls, and 59 typically developing (TD) controls between 3 to 25 years of age. An eye tracking paradigm was administered to all participants, with the ASD group completing the paradigm a second time approximately two months later. Participants’ average proportion of looking and number of fixations to specific areas of interest (AOI) were examined along with changes in pupil reactivity while viewing different emotional faces. Results suggest atypical visual scanning through reduced proportion of looking and number of fixations in the in the ASD group regardless of the emotion that was presented. The ASD group exhibited a similar facial scanning profile in comparison to the DD group, suggesting additional work is needed to delineate the role of cognitive functioning on social attention in ASD. Further, pupillometry measures were able to detect increases in pupil dilation to happy faces in the ASD group. Lastly, test-retest reliability coefficients varied between the poor and excellent range based on the mechanism assessed, with proportion of looking toward the eyes and mouth demonstrating the highest reliability coefficients. These findings build on the promise of eye tracking as a feasible and reliable biomarker for identifying social attention and emotion recognition deficits in ASD. Detecting differences in emotion recognition explicitly through visual scanning was not clear. Specific mechanisms within the eye tracking paradigm may be viable options for assessing treatment-specific outcomes.